2015
DOI: 10.1266/ggs.14-00063
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent diversities between nuclear and plastid genomes of AA genome species in the genus <i>Oryza</i>

Abstract: . glumaepatula were phylogenetically close to each other and carried low genetic diversity. They were separated from independent lineages, suggesting that they had diverged from a single ancestral maternal lineage, but diverged later to keep gene flow within respective species, as SSR compositions suggested. Genetic relationships among AA genome species indicate how these species have evolved and become distributed across four continents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In the current study, we found six groups of African rice and that the group membership of the O. barthii samples generally agrees with their country of origin but not ecology. However, nearly 40% of the O. barthii accessions were clustered together with African rice accessions, which differed between the current study and other studies (Orjuela et al 2014 ; Wang et al 2014 ), which may be due to differences in the genetic background of the germplasm and sample size (Iwamoto et al 1999 ; Lu et al 2000 ; Nagano et al 2000 ; Ishii et al 2001 ; Park et al 2003 ; Ren et al 2003 ; Zhu and Ge 2005 ; Duan et al 2007 ; Zhang et al 2014 ; Wambugu et al 2015 ; Yin et al 2016 ).…”
Section: Discussionmentioning
confidence: 54%
“…In the current study, we found six groups of African rice and that the group membership of the O. barthii samples generally agrees with their country of origin but not ecology. However, nearly 40% of the O. barthii accessions were clustered together with African rice accessions, which differed between the current study and other studies (Orjuela et al 2014 ; Wang et al 2014 ), which may be due to differences in the genetic background of the germplasm and sample size (Iwamoto et al 1999 ; Lu et al 2000 ; Nagano et al 2000 ; Ishii et al 2001 ; Park et al 2003 ; Ren et al 2003 ; Zhu and Ge 2005 ; Duan et al 2007 ; Zhang et al 2014 ; Wambugu et al 2015 ; Yin et al 2016 ).…”
Section: Discussionmentioning
confidence: 54%
“…Thus, the evolutionary lineage depicted by the phylogenetic tree based on mitochondrial DNA might not precisely mirror the actual evolutionary ties. Given its semi-autonomous genetic framework, mitochondria may display divergent evolutionary trajectories compared to the nuclear or chloroplast genomes [ 55 57 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Based on whole genome sequencing of 3,024 accessions of O. sativa (IRRI 3K SNP project) and 446 accessions of O. rufipogon (Oryza base, NIG), O. rufipogon and O. sativa shared the same one base T-deletion in the S-type intron 20 sequences (Fig. 3A), because there was no SNP in the intron 20 between columns BF and BG in Supplemental 3A), it might be originated with relation to O. rufipogon (Vaughan et al 2005, Yin et al 2015. Two cultivated species, O. sativa and O. glaberrima, were independently originated from O. rufipogon in South-east Asia and O. barthii in West Africa, respectively.…”
Section: Resultsmentioning
confidence: 99%